Characterization of silicate scale formation: The effect of pH on silica/silicate scale formation / Muhammad Farid Mohd Yazid … [et al.] - Mohd Yazid, Muhammad Farid; Sazali, Rozana Azrina; Sorbie, Kenneth Stuart; Boak, Lorraine Scott; Zainal Abidin, Mohd Zaki; Azizi, Azlinda (Universiti Teknologi MARA Shah Alam, 2022)
One of the challenging situations that engineers have been encountered in the oil and gas industry is the formation of silicate scale during alkaline surfactant polymer (ASP) flooding which could be throughout the overall production system, from upstream to downstream processes. In the ASP flooding, the ASP slug is injected into the reservoir at a high pH, which is later mixed up with the connate water causing the pH condition inside the reservoir to be reduced. This reduction of pH will aggravate the precipitation of silicate scaling as this type of scale is very much pH-dependent, with the presence of the metallic ion worsening. The main objectives of this study are to characterise and compare (with the pure commercial) the precipitates produced from the Si/Mg system at various pH conditions using spectroscopic analysis, as well as to study the mechanism of silicate scale formation. The precipitates were reproduced from a-Si/Mg scaling brine at room temperature under various pH test conditions. The spectroscopic results confirmed the variation of pH as it propagates within the reservoir from the injection to the production well, producing a different type of morphology. The results obtained showed that pH affects the types and morphology of the precipitation significantly, where the formation of silica/silicate scale is most severe when the value of pH increases whilst Mg-silicate scaling favours pH 8.5.